Involvement of Peripheral Serotonin in Blood Cells in Healthy Cyclical Mares of Different Ages - Katiuska Satué; Deborah La Fauci; Pietro Medica; María Gemma Velasco-Martínez; Giuliana Barbiera; Esterina Fazio (Veterinary Sciences, 2025)
The estrous cycle involves hormonal fluctuations that influence serotonin (5-HT) concentrations and immune cell activity. During the follicular phase, estrogen increases 5-HT synthesis, enhancing cellular responses to inflammation. In contrast, in the luteal phase, progesterone suppresses immune function, reducing 5-HT availability. Age-related changes in hormone concentrations can affect these processes, potentially altering cellular responses and 5-HT dynamics in the oldest females. This study hypothesizes the relationship between 5-HT and blood cells in healthy cyclic mares, considering age as an influencing factor. Understanding these interactions offers insights into reproductive health and immune regulation in equine species. The aim was to describe the interaction between 5-HT and blood cells in twenty-five healthy cyclic Spanish Purebred mares, evaluating the effect of aging. For this purpose, the mares were classified into two age groups as follows: from 4 to 9 years (n = 12 younger mares) and from 10 to 15 years (n = 13 older mares). Younger and older mares showed an opposite 5-HT trend at +5 and +16 day of cycle (d), with greater concentrations in younger mares (p < 0.05) and lower values in older mares (p < 0.05) than at −5 and 0 d. Older mares showed a lower 5-HT concentration at +5 and +16 d (p < 0.05) than younger mares. Mares of both ages showed a superimposed WBC trend, with the greatest number both at −5 and 0 d (p < 0.05). Older mares showed a lower WBC number at −5 d (p < 0.05), and lower NFS and LYMPH numbers both at +5 and +16 d (p < 0.05) than younger mares; the latter showed the lowest NFS number at +16 d, and LYMPH number at +5 and +16 d. Mares of both ages showed a similar trend for the N/L ratio. Older mares showed a lower MON number at +5 d (p < 0.05), greater PLTs at +5 and +16 d (p < 0.05) than younger mares, and a greater PLT number at −5 and 0 d than at +5 and +16 d (p < 0.05). The activity of 5-HT is regulated by its rate of synthesis, release, and metabolism according to age. Aging reduced the 5-HT concentrations and the number of WBCs, NFSs, LYMPHs, and MONs, inducing correlations among these and 5-HT in healthy young and old cyclic mares.